Pengembangan Aplikasi Bee_Ba for Fun untuk Membaca Permulaan dengan Metode Suku Kata di Sekolah Dasar - Yuni Triana Dewi (Jurnal Syntax Admiration, 2023)
For some students, mastering beginning reading skills with the syllabic method can be a challenge that requires a creative and engaging approach. Therefore, this study aims to develop the Bee_Ba For Fun application as a fun tool to assist elementary students in learning beginning reading with the syllabic method. This application development method is based on a software design approach that involves the stages of requirements analysis, conceptual design, implementation, testing, and evaluation. Bee_Ba For Fun app development uses the latest technology in software development and interface design that appeals to elementary students. This application is designed to be accessible through mobile devices such as smartphones or tablets, so students can learn to read beginning with the syllabic method flexibly and interactively. The Bee_Ba For Fun application is equipped with interesting features, such as interactive word games, selection of difficulty levels tailored to students' abilities, and awards given as a form of motivation. In addition, this application is also equipped with learning materials that are arranged systematically, ranging from simple syllables to more complex syllables. Thus, students can learn beginning reading progressively and enjoyably. This research also involved testing the application by involving elementary school students as participants. The results of this trial will be used to evaluate the effectiveness and efficiency of the Bee_Ba For Fun app in helping students master beginning reading with the syllable method. It is hoped that this application can be an effective and entertaining learning resource for elementary students, as well as increase their interest in reading learning